Implementasi PSAK109 tentangAkuntansi Zakat Dan Infak/Sedekah Pada LAZ (Studi Kasus LAZIS Muhammadiyah Sumatera Barat) - Adrian Diva Fanani (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Andalas, 2024)
This research aims to understand the implementation of Statement Number 109 of Accounting Standard on Zakat and Infaq/Sadaqah (PSAK 109) at LAZIS Muhammadiyah Sumatera Barat and to identify obstacles faced in implementing it. This research used a qualitative research approach and inductive reasoning. The results of this study indicated that LAZIS Muhammadiyah Sumatera Barat has adopted some provisions of PSAK 109 in its financial reports. These findings imply that adhering to the prescribed financial report format can prevent material misstatements. This research contributes by identifying deficiencies in the financial reports of LAZIS Muhammadiyah in terms of compliance with the provisions of PSAK 109 on Zakat and Infaq/Sadaqah Accounting.